2013
DOI: 10.2337/dc12-0850
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Is Associated With Cardiovascular, Renal, Retinal, and Autonomic Disease in Type 1 Diabetes

Abstract: OBJECTIVEIn patients with type 1 diabetes, we investigated the association between arterial stiffness and diabetes complications.RESEARCH DESIGN AND METHODSThis was a cross-sectional study including 676 Caucasian patients with type 1 diabetes (374 [55%] men, aged 54 ± 13 years [mean ± SD]) and 51 nondiabetic controls (28 [55%] men, aged 47 ± 13 years). Aortic pulse wave velocity (PWV) was measured with SphygmoCor (AtCor Medical, Sydney, Australia) for 635 patients and all 51 controls.RESULTSPWVs (mean ± SD) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 40 publications
6
74
1
3
Order By: Relevance
“…Similarly, previous studies performed in populations of young people with type 1 diabetes mainly showed differences in cIMT or FMD when comparing subjects with and without microalbuminuria (23). Our results are also in line with data from adults with type 1 diabetes, where PWV was one of the first detectable vascular alterations in those with microalbuminuria and macroalbuminuria (24). Increased PWV has emerged as a predictor of future CV events and mortality (24).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, previous studies performed in populations of young people with type 1 diabetes mainly showed differences in cIMT or FMD when comparing subjects with and without microalbuminuria (23). Our results are also in line with data from adults with type 1 diabetes, where PWV was one of the first detectable vascular alterations in those with microalbuminuria and macroalbuminuria (24). Increased PWV has emerged as a predictor of future CV events and mortality (24).…”
Section: Discussionsupporting
confidence: 80%
“…Our results are also in line with data from adults with type 1 diabetes, where PWV was one of the first detectable vascular alterations in those with microalbuminuria and macroalbuminuria (24). Increased PWV has emerged as a predictor of future CV events and mortality (24). The vascular reassessment at the end of AdDIT will test the hypothesis that PWV evolution at a very young age can be modified through early treatment with ACEIs and statins, both alone and in combination.…”
Section: Discussionsupporting
confidence: 76%
“…87) In addition, in a cohort of young, type 1 diabetic subjects without a history of hypertension and any evidence of macrovascular disease, subjects with a high cardiac autonomic neuropathy score had signifi cantly higher pulse wave velocity compared with subjects with a low score, and a negative correlation between pulse wave velocity and heart rate variation was observed. 88) These fi ndings may help to explain the high cardiovascular mortality seen in diabetic subjects with autonomic neuropathy. 87) Indeed, impaired cardiac autonomic control is statistically signifi cantly related to the development of ischemic heart disease among individuals with diabetes, independent of markers of the duration/severity of glucose metabolism impairments.…”
Section: Interaction Between Vascular Function and The Ans In Subjectmentioning
confidence: 99%
“…In the study of Theilade et al [18] a positive correlation between PWV and excretion ratio was found. Also it was seen in the same study that in normoalbuminuric type 1 DM patients, PWV was relatively high in comparison to control group.…”
Section: Discussionmentioning
confidence: 96%
“…[17] In this study a statistically positive relation was diagnosed between PWV and type 2 DM duration, HDL, SBP, MAP values. In a study by Theilade et al [18] in type 1 DM patients, a positive correlation (r=0.54) between PWV and diabetes duration was seen. In a study by Cruickshank et al [19] it was seen that as glucose tolerance fell, PWV values rose.…”
Section: Discussionmentioning
confidence: 99%